2008
DOI: 10.1002/ejoc.200701115
|View full text |Cite
|
Sign up to set email alerts
|

Functionalized 2,5‐Dipyridinylpyrroles by Electrochemical Reduction of 3,6‐Dipyridinylpyridazine Precursors

Abstract: The ring contraction of pyridinylpyridazine derivatives into the corresponding pyrroles by electrochemical reduction was studied, and the influence of the substituents of the pyridazine precursors on the process is discussed. Cyclic voltammetry studies underlines the electron-withdrawing or -donating effect of the substituent on the pyridazine ring, which determines the reaction pathway of their preparative electrolysis. The ring-contraction process, with extrusion of nitrogen, proceeds by two subsequent two-e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0
4

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 33 publications
2
23
0
4
Order By: Relevance
“… 28 pyTz was prepared according to a Pinner-type synthesis described in the literature. 19,29 Substrates 1 (norbornene), 2 (5-norbornene-2-methanol), 9 ((±)- endo , exo -dimethyl-5-norbornene-2,3-dicarboxylate), 14 (dicyclopentadiene), 15 (cyclopentene), 16 (1-hexene) and 17 (styrene) were obtained from commercial sources (Sigma–Aldrich, Fluka, ABCR, Alfa Aesar) and used without further purification.…”
Section: Methodsmentioning
confidence: 99%
“… 28 pyTz was prepared according to a Pinner-type synthesis described in the literature. 19,29 Substrates 1 (norbornene), 2 (5-norbornene-2-methanol), 9 ((±)- endo , exo -dimethyl-5-norbornene-2,3-dicarboxylate), 14 (dicyclopentadiene), 15 (cyclopentene), 16 (1-hexene) and 17 (styrene) were obtained from commercial sources (Sigma–Aldrich, Fluka, ABCR, Alfa Aesar) and used without further purification.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, changing the 1,2,4triazine substituent in BTP ligands to a 1,2,4,5-tetrazine substituent increases the substituent's symmetry, opening new pathways for a simple synthesis. 38,39 Our previous results on the extraction performance have shown that ligands 1 and 2 are able to separate Am(III) from Eu(III). 40 However, their selectivity is significantly lower in comparison to BTPligands (SF Am/Eu (Et-BDP) = 5, 40 SF Am/Eu ( n Pr-Tetrazine) = 9, 40 SF Am/Eu ( n Pr-BTP) > 100 13,14,27 ).…”
Section: Introductionmentioning
confidence: 99%
“…[10] While the generality of this approach is not obvious, we have succeeded in effecting the electroreduction-driven ring contraction of several 3,6-substituted pyridazines to the corresponding 2,5-substituted pyr-roles. [11] As an extension of this "green" methodology, we report here on efficient access to expanded 2,6-bis[5-(pyridin-2-yl)pyrrol-2-yl]pyridines 1 a-c by electrochemical ring contraction of the corresponding 2,6-bis[6-(pyridin-2-yl)pyridazin-3-yl]pyridines 2 a-c (Scheme 1). These alternating pyrrolic sequences flanked by three pyridine units are useful tools to provide original nitrogen-based donor-acceptor ligands of great interest in both photochemistry and biology.…”
Section: Introductionmentioning
confidence: 99%